The influence of progression of atrial fibrillation on quality of life: a report from the Euro Heart Survey. Issue 6 (19th July 2017) - Dudink, Elton A M P; Erküner, Ömer; Berg, Jenny; Nieuwlaat, Robby; de Vos, Cees B; Weijs, Bob; Capucci, Alessandro; Camm, A John; Breithardt, Günter; Le Heuzey, Jean-Yves; Luermans, Justin G L M; Crijns, Harry J G M
Abstract: Aims: Progression of atrial fibrillation (AF) from paroxysmal to persistent forms is an active field of research. The influence of AF progression on health related quality of life (HRQoL) is currently unknown. We aimed to assess the influence of AF progression on HRQoL, and whether this association is mediated through symptoms, treatment, and major adverse events. Methods and results: In the Euro Heart Survey, 967 patients were included with paroxysmal AF who filled out EuroQoL-5D at baseline and at 1 year follow-up. Those who progressed ( n  = 132, 13.6%) developed more problems during follow-up than those who did not, on all EuroQoL-5D domains (increase in problems on mobility 20.5% vs. 11.4%; self-care 12.9% vs. 6.2%; usual activities 23.5% vs. 14.0%; pain/discomfort 20.5% vs. 13.7%; and anxiety/depression 22.7% vs. 15.7%; all P  < 0.05), leading to a decrease in utility [baseline 0.744 ± 0.26, follow-up 0.674 ± 0.36; difference −0.07 (95% CI [−0.126, −0.013], P  = 0.02)]. Multivariate analysis showed that the effect of progression on utility is mediated by a large effect of adverse events [stroke (−0.27 (95% CI [−0.43, −0.11]); P  = 0.001], heart failure [−0.12 (95% CI [−0.20, −0.05]); P  = 0.001], malignancy (−0.31 (95% CI [−0.56, −0.05]); P  = 0.02] or implantation of an implantable cardiac defibrillator [−0.12 (95% CI [−0.23, −0.02]); P  = 0.03)], as well as symptomatic AF [−0.04 (95% CI [−0.08, −0.01]); P  = 0.008]. Conclusion: AF progression is associated with a decrease in HRQoL. However, multivariate analysis revealed that AF progression itself does not have a negative effect on HRQoL, but that this effect can be attributed to a minor effect of the associated symptoms and a major effect of associated adverse events.